Ida the incredible ironing board - Marsden, Jo. (Dublin : Hoo Ha House, 2006)
Ida the ironing board has a funny walk, so she hides away in her cupboard. "I don't like it when anyone stares" she said. But can she brave the stares when someone needs her help?